Application of 16S rDNA metagenomic library for source-tracking of fecal pollution in selected stations and tributaries of Manila Bay, Philippines - dela Peña, Laurice Beatrice Raphaelle O.; Mamawal, Diana Rose D.; Nacario, Mae Ashley G.; Vejano, Mark Raymond A.; Rivera, Windell L. (Frontiers in Water, 2025)
Fecal contamination of important water resources poses a significant public health concern. To protect the public’s health, the dominant sources and various factors that contribute to pathogenesis and fecal contamination must be assessed. This study aimed to assess the effectiveness of 16S rRNA gene amplicon sequencing in detecting pathogens and tracking their sources in Manila Bay, Philippines. We sequenced the 16S V3–V4 region from DNA extracts of fecal samples (n = 37) of chickens, ducks, pigs, cows, goats, dogs, and sewage; and environmental water sources (n = 55) from Manila Bay tributary rivers, coastal stations, and offshore sites, which represented the “source” and “sink” samples, respectively. We used SourceTracker2 to estimate the percent contribution of these sources to the microbial community in Manila Bay. Among the detected bacteria were human and animal pathogens, including Clostridiales, Alteromonadales, Campylobacterales, Pseudomonadales, and Aeromonadales. Phosphates, fecal coliform, and dissolved oxygen were the major drivers of the top bacterial groups. Microbial community signatures clustered according to their corresponding sample types based on the beta diversity distances, suggesting the potential application of source libraries for analyzing the sink samples. Validation of the fecal source library shows that SourceTracker2 correctly predicted the contribution of the six fecal sources, but had a lower distinction for bovine sources. Sewage accounted for 93% of the contamination in Manila Bay, followed by ducks (5.6%), indicating human waste as the primary source. This study demonstrates the utility of microbial source tracking in targeted water quality management strategies.